Rehabilitation and Repair of AL- Tahera Church in AL- Hamdaniya District, Mosul City, Iraq - Emad Noel Naoom (Elsevier, 2022)
The heritage ancient buildings are part of the Iraqis history and their preservation is important for the survival of this history. Many places of worship in Iraq are vandalized and burned during the ISIS period occupation of Iraq (2014–2016). Al-Tahira Church in Al-Hamdaniya / Mosul is one of the burnsed churches. The burning leads to reducing the bearing resistance of the supporting columns and arches made of local marble due to the formation of fractures and the appearance of cracks in these columns. In situ and laboratory examinations were performed to determine the mechanism of qualifying these columns and arches. Injections were made with low-viscosity epoxy materials to fill the cracks. The columns are laminated using a framing system consisting of sheet metal and cement-based mortar, take into account a strengthening of the arches during the maintenance period to prevent them from collapsing. The arches are lined with the same original materials, taking care to avoid any additional loads on them. The method strengthening of columns proved its success as the cross-sections of these columns were transformed from a monolithic (made from local marble) to a composite (steel covered by the local marble). A visual inspection was adopted to give the acceptance document for rehabilitation and maintenance work for the columns and arches for 18 months. As a result of no engineering or construction defects are noticed during this period, permission is given to continuing the rehabilitation work for the rest of the work items.